Clinico‐pathological factors influencing lymph node yield in colorectal cancer and impact on survival: Analysis of new zealand cancer registry data. Issue 4 (8th February 2015) - Ahmadi, Omid; Stringer, Mark D.; Black, Michael A.; McCall, John L.
<x xml:space="preserve">Abstract</x> Background Lymph node yield (LNY) and lymph node ratio (LNR) are recognized as independent prognostic factors in colorectal cancer (CRC). Objectives To examine the relationship between LNY and other clinico‐pathological variables, and the prognostic value of LNY and LNR on patient survival in CRC. Methods The clinico‐pathological and survival data for patients diagnosed from January 2000 to July 2012 were retrieved from the New Zealand Cancer Registry. Multiple linear regression was used to identify clinico‐pathological factors influencing LNY, and Cox regression was used to determine the association between LNY and LNR and patient survival. Results 14, 646 patients were included in the study (mean age 70.3 years, 50.1% male). Mean LNY was 17.4. Younger age, right‐sided disease, higher T stage, female sex and no neoadjuvant radiotherapy (rectal cancer) were all associated with higher LNY (P ≤ 0.001). Overall survival in Stage I‐III disease increased with higher LNY (for LNY ≥ 12, HR = 0.67, 95% CI 0.64–0.72; P < 0.001). Survival in Stage III‐IV disease was inversely related to LNR (HR = 0.56, 95% CI 0.51–0.62; P < 0.001). Conclusion LNY is influenced by patient age, site of disease and T stage. LNY (Stage I‐II) and LNR (Stage III‐IV) have independent prognostic value in CRC. J. Surg. Oncol. 2015 111:451–458. © 2015 Wiley Periodicals, Inc.